Бошланғич синф ўқувчиларида дарсларнинг матн билан боғлиқ босқичларга қизиқиш уйғотиш - Пирниязова, Ш.О (SCIENCE and SOCIETY, 2024)
This article deals with arousing interest in text-related stages in mother tongue classes in primary school students and arousing sustained interest in types of work by creating motivation in students.
Keywords: text; lesson; exercise; stage; knowledge; interest; motive; methodology; task; reading; listening